2013
DOI: 10.1038/jcbfm.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging of Bilateral Anterior Capsulotomy in Refractory Obsessive Compulsive Disorder: an FDG PET Study

Abstract: The therapeutic benefits of bilateral capsulotomy for the treatment of refractory obsessive compulsive disorder (OCD) are probably attributed to interruption of the cortico-striato-thalamo-cortical circuitry. We evaluated resting brain metabolism and treatment response in OCD patients using positron emission tomography (PET) imaging. [(18)F]-fluoro-deoxy-glucose PET was performed in eight OCD patients precapsulotomy and postcapsulotomy. We determined metabolic differences between preoperative images in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 35 publications
(48 reference statements)
3
38
1
1
Order By: Relevance
“…Zuo et al also showed a metabolic decrease in the ACC after capsulotomy in OCD patients (12). The anterior cingulate has been described as an important region in both OCD and MD symptomatology.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Zuo et al also showed a metabolic decrease in the ACC after capsulotomy in OCD patients (12). The anterior cingulate has been described as an important region in both OCD and MD symptomatology.…”
Section: Discussionmentioning
confidence: 94%
“…There was no overlap with the frontal regions of decreased metabolism at baseline. Chronic successful treatment has been associated with a decrease in prefrontal and orbitofrontal metabolism in several studies (12,30,31). This decrease correlated with improvement of OCD symptoms in several studies (8,30).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations